GIS and f-AHP Integration for Locating a New Textile Manufacturing Facility - Onden, Ismail; Eldemir, Fahrettin (INST CHEMICAL FIBRES, 2015)
Location analysis for a textile manufacturing facility is a strategic decision due to its long-term effects on profitability, accessibility, and sustainability. Thus an analysis should be made using a comprehensive approach. The facility location selection problem can be represented with a multi-criteria structure. This study considered locating a new manufacturing facility and accepted seven decision criteria as decision parameters. Istanbul was the study area, and seven candidate locations were considered to start a new manufacturing facility. During the evaluation process, Geographic Information Systems and the fuzzy analytic hierarchy process were combined to order the preference levels of candidate areas. A novel methodology for the textile industry is proposed to integrate experts' thoughts and geographic information.
Keywords: textile facility selection; location analysis; geographic information systems (GIS); fuzzy analytic hierarchy process (f-AHP); SITE SELECTION; MULTICRITERIA EVALUATION; INFORMATION-SYSTEMS; DECISION-MAKING; FUZZY AHP; Materials Science